Assessing public policy and neutrality of the state civil apparatus in Indonesian elections - Elpisina , Elpisina; Muhammad, Pauzi (Goodwood Publishing, 2025)
Purpose: State civil servants have the right to vote in elections, but they are required to be neutral and professional in carrying out their duties and repetition, namely implementing public policies and providing public services to the community without being involved in practical political processes on the election agenda. Research/methodology: : The method used was a normative legal research method. This research method is carried out in several ways, namely, conducting studies, describing, interpreting, systematizing, and assessing and analyzing positive law. Results: The results of this research are regulations regarding the neutrality of the State Civil Apparatus as regulated by Law Number 7 of 2017 concerning General Elections, PP No. 42/2004 concerning the Development of Corps Spirit and the Code of Ethics for Civil Servants, PP No. 42/2004 concerning the Development of Corps Spirit and the Code of Ethics for Civil Servants, PP No. 53/2010 concerning Civil Servant Discipline, Law No. 5/2014 concerning State Civil Apparatus, and a circular letter from the Minister of State Apparatus Empowerment and Bureaucratic Reform No. 1 of 2023 concerning the Guidance and Supervision of Neutrality of Non-Civil Servants in the Implementation of General Elections and Elections. Conclusions: This study increases knowledge about the neutrality of state civil apparatuses in general elections based on Laws and Government Regulations. This study also provides information for policymakers to understand the neutrality of the State Civil Service in General Elections, so that democracy in Indonesia will improve. Limitations: This study only covers the neutrality of State Civil Apparatus in General Elections; Therefore, expanding the research to the Indonesian National Army and the Republic of Indonesia Police could produce comprehensive findings. Contribution: This study provides legal insights and policy recommendations to strengthen the neutrality of civil servants and support fair and democratic elections in Indonesia.